PENGARUH SOSIAL EKONOMI TERHADAP KINERJA GURU FISIKA SMA NEGERI TERAKREDITASI A DI KABUPATEN KAMPAR - Hamka, Defrizal Defri (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2022)
This study aims to describe the physics teacher’s performance at Public Senior High Schools accredited “A” in Kampar Regency based on the competence of teacher’s, instructional planning, implementation of learning, and learning assessment, control of competencies, and the socioeconomic status and the physics teacher’s performance at Public Senior High Schools accredited “A” in Kampar Regency. This was an corelation study employing the quantitative descriptive technique. The study was carried out in public senior high school in Kampar Regency with the research subjects of physics teacher’s who teach at Public Senior High Schools accredited “A” in Kampar Regency. The data were collected though a questionnaires, documentation, and observation. They were analyzed by means in this research of the descriptive statistical technique using percentages and Spearman correlation analysis. The results of the study show that: (1) physics teacher’s performance at Public Senior High Schools accredited “A” in Kampar Regency in the planning and implementation of learning are in the the very good category, meanwhile, the learning assessment in the good category. (2) performance of physics teacher’s at Public Senior High Schools accredited “A” in Kampar Regency on four competencies based on teachers' self-assessment and principals assessment are in the very good category. (3) socio-economic status has a strong correlation (positive) and significant to the physics teacher’s performance at Public High School accredited “A” in Kampar regency.